2014
DOI: 10.1044/2014_jslhr-s-12-0265
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Correlates of Speech Versus Nonspeech Tasks in Children and Adults

Abstract: Purpose To assess autonomic arousal associated with speech and nonspeech tasks in school-age children and young adults. Method Measures of autonomic arousal (electrodermal level, electrodermal response amplitude, blood pulse volume, and heart rate) were recorded prior to, during, and after the performance of speech and nonspeech tasks by twenty 7- to 9-year-old children and twenty 18- to 22-year-old adults. Results Across age groups, autonomic arousal was higher for speech tasks compared with nonspeech tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“… 5 Consistent with some of these findings re AWS, related studies of adults who do not stutter and children who do not stutter Arnold et al (2014) and Kleinow & Smith (2006) reported higher autonomic arousal during challenging speaking conditions relative to other non-speaking conditions and non-challenging speaking conditions. …”
mentioning
confidence: 63%
See 3 more Smart Citations
“… 5 Consistent with some of these findings re AWS, related studies of adults who do not stutter and children who do not stutter Arnold et al (2014) and Kleinow & Smith (2006) reported higher autonomic arousal during challenging speaking conditions relative to other non-speaking conditions and non-challenging speaking conditions. …”
mentioning
confidence: 63%
“…Interestingly, they found that children, when compared to adults, exhibited greater autonomic arousal as well as greater variability in their speech motor coordination, activity apparently associated with a less mature cognitive and linguistic system. Similarly, in a recent study of autonomic arousal of children and adults in speech and non-speech tasks, Arnold, MacPherson, & Smith (2014) reported that both children and adults demonstrated higher arousal for speech than non-speech tasks. In addition, Arnold et al (2014) found gender differences in children’s ANS activity during speaking tasks (i.e., higher arousal in boys than girls during a complex narrative task), a finding attributed to gender differences in speech and language skills.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Second, the selected measures are established within the speech production literature and have been shown to be sensitive to speech production demands. 23, 31, 77 …”
Section: Methodsmentioning
confidence: 99%